PENGARUH PEMAHAMAN SAK EMKM DAN KESIAPAN PELAKU UMKM TERHADAP MINAT IMPLEMENTASI SAK EMKM - Firloy, Rani; Sososutiksno, Christina; Limba, Franco (Jurnal Kajian Ekonomi dan Manajemen Indonesia (JKEMI), 2023)
This study aims to empirically examine the Effect of Understanding SAK EMKM and Readiness of MSME Actors on Interest in Implementing SAK EMKM. This study used quantitative research with a descriptive approach. Sampling technique using nonprobability sampling with accidental sampling. This study processed primary data obtained using questionnaires distributed to 73 MSME actors in Aru Islands Regency obtained using the Slovin technique. The tool used to analyze the relationship of variables in this study was SPSS V.25. The results of this study show that the Understanding of EMKM SAK and the Readiness of MSME Actors have a positive and significant effect on the Interest in the Implementation of EMKM SAK in the Aru Islands Regency consisting of micro and small enterprises